Pharmacokinetics of mebendazole in plasma and cerebrospinal fluid following a single oral dose in healthy dogs - Yanke, Amy B.; Day, Kendall E.; Taylor, Amanda R.; Cruz-Espindola, Crisanta; Boothe, Dawn M. (Frontiers in Veterinary Science, 2023)
Novel therapies are needed for treatment of gliomas. Mebendazole previously demonstrated anti-neoplastic effects on canine glioma cell lines at in vitro mean inhibitory concentrations (IC50) of 10 ng/ml. Our study aimed to titrate the oral dose of mebendazole necessary to achieve concentrations >10 ng/ml in cerebrospinal fluid (CSF) of healthy dogs. We hypothesized that an oral dose up to 200 mg/kg would be necessary. Phase one was a dose titration study using a total of 6 mixed breed dogs that described dose versus plasma concentrations for 72 hours after single oral dosing of either 50 mg/kg (n=2), 100 mg/kg (n=2), or 200 mg/kg (n=2). Based on phase one, phase two dogs (total of 9) received 100 mg/kg (n=4) or 200 mg/kg (n=5) orally and blood samples were collected intermittently for 60 hours with CSF samples collected intermittently for 24 hours. Mebendazole was quantitated in plasma and CSF using high performance liquid chromatography. Median peak plasma concentrations (Cmax) were reached at 7 + 2 hours (100 mg/kg) of 220 ng/ml (81, 283) and at 15 + 4 hours (200 mg/kg) of 147 ng/ml (112, 298). The respective area under the curve (AUC: ng/ml/hr) reported as a median was 2119 (1876, 3288) vs 3115 (1559, 4972). Median plasma concentrations (ng/ml) for 100 vs 200 mg/kg were 47 (32, 52) vs 65 (35, 104), respectively. For CSF, the median value for Cmax (at 100 mg/kg vs 200 mg/kg) was 8 (2, 28) vs 21 (12, 27) and AUC was 87 (22, 157) vs 345 (92, 372), respectively. Relative bioavailability in CSF versus plasma was 4 to 10%. Although several animals demonstrated clinical signs indicative of gastrointestinal upset (i.e., vomiting (n=2), diarrhea (n=2), or both (n=1)), these events were not considered serious. The in vitro IC50 for gliomas can be reached in CSF at 100 mg/kg (n=1), however a 200 mg/kg dose yielded more consistent concentrations.